Empowered! : Latinos Transforming Arizona Politics - Magaña, Lisa; Silva, Cesar S., 1982- (Book collections on Project MUSE., 2021)
"Empowered! examines Arizona's recent political history and how it has been shaped and propelled by Latinos. This book shows how Latinos are mobilizing to counter proposals for Draconian immigration laws with new and innovative approaches"--